Platelet-Derived Growth Factor D Is a Prognostic Biomarker and Is Associated With Platinum Resistance in Epithelial Ovarian Cancer. Issue 2 (February 2018) - Zhang, Mengjun; Liu, Tianbo; Xia, Bairong; Yang, Chunyan; Hou, Siyu; Xie, Wanlin; Lou, Ge
Abstract : Objective: This study aimed to investigate whether platelet-derived growth factor D (PDGF-D) is a prognostic biomarker and is associated with platinum resistance in epithelial ovarian cancer, which has not been studied by others previously. Methods: In this study, we detected expression of PDGF-D in ovarian cancer tissues through immunohistochemistry and Western blotting. Furthermore, we analyzed the association between PDGF-D expression and clinicopathological features including prognosis in epithelial ovarian cancer. Statistical analyses were performed by using χ 2 test, log-rank test, Cox regression test, and Kaplan-Meier method. Results: High PDGF-D expression is positively correlated with International Federation of Gynecology and Obstetrics stage ( P < 0.001), histologic grade ( P < 0.001), lymph node metastasis ( P = 0.022), and poor prognosis ( P < 0.001). Platelet-derived growth factor D in platinum-resistant cases is overexpressed compared with that in platinum-sensitive cases ( P < 0.001). Obstetrics stage ( P = 0.029) and PDGF-D overexpression ( P < 0.001) are independently correlated with platinum resistance. Conclusions: Our study indicates that PDGF-D overexpression is an independent predictor of platinum-based chemotherapy resistance and that it may also be a potential biomarker for targeted therapy and poor prognosis.